Phytochemicals, biological activity, and industrial application of lotus seedpod (Receptaculum Nelumbinis): A review - Wang, Yi-Fei; Shen, Zi-Chun; Li, Jing; Liang, Tian; Lin, Xiao-Fan; Li, Yan-Ping; Zeng, Wei; Zou, Qi; Shen, Jian-Lin; Wang, Xiao-Yin (Frontiers in Nutrition, 2022)
Lotus (Nelumbo nucifera Gaertn.) is a well-known food and medicinal plant. Lotus seedpod (Receptaculum Nelumbinis) is the by-products during lotus products processing, which is considered as waste. Numerous studies have been conducted on its phytochemicals, biological activity and industrial application. However, the information on lotus seedpod is scattered and has been rarely summarized. In this review, summaries on preparation and identification of phytochemicals, the biological activities of extracts and phytochemicals, and applications of raw material, extracts and phytochemicals for lotus seedpod were made. Meanwhile, the future study trend was proposed. Recent evidence indicated that lotus seedpods extracts, obtained by non-organic and organic solvents, possessed several activities, which were influenced by extraction solvents and methods. Lotus seedpods were rich in phytochemicals categorized as different chemical groups, such as proanthocyanidins, oligomeric procyanidins, flavonoids, alkaloids, terpenoids, etc. These phytochemicals exhibited various bioactivities, including ameliorating cognitive impairment, antioxidation, antibacterial, anti-glycative, neuroprotection, anti-tyrosinase and other activities. Raw material, extracts and phytochemicals of lotus seedpods could be utilized as sources for biochar and biomass material, in food industry and as dye. This review gives well-understanding on lotus seedpod, and provides theoretical basis for its future research and application.